Short-lived Bakevelliid-Sea in the Aptian Romualdo Formation, Araripe Basin, northeastern Brazil - Rodrigues, M. G. [UNESP]; Matos, S. A. [UNESP]; Varejao, F. G.; Fuersich, F. T.; Warren, L. V. [UNESP]; Assine, M. L. [UNESP]; Simoes, M. G. [UNESP] (Elsevier B.V., 2020)
New Aptian (Lower Cretaceous) bakevelliid bivalves are described for the Romualdo Formation, Santana Group, Araripe Basin, northeastern Brazil. Together with the other known member of the family Bakevelliidae, already recorded from the unit (i.e., Aguileria dissita), the new bivalves (Araripevellia musculosa gen. et sp. nov., Aguileria romualdoensis sp. nov., and Gen. et sp. indet.) indicate that the Romualdo bakevelliid fauna was more diverse than previously realized. Bakevelliid-rich carbonates, some with specimens preserved in situ, are restricted to the upper third of this unit, a stratigraphic interval yielding also echinoderm-, gastropod- and stromatolite-bearing limestones. These pteriomorphian bivalves were widely distributed in the Romualdo Formation and are a testimony of the short-lived Bakevelliid-Sea that flooded the whole Araripe Basin during the Aptian. Notably, Aguileria romualdoensis sp. nov. closely resembles Aguileria renauxiana from the Cenomanian Woodbine Formation, Texas, US. In addition, Aguileria dissita is also recorded in the upper Aptian Albian Riachuelo Formation of the Sergipe-Alagoas Basin. Together with other macroinvertebrates (i.e., gastropods, echinoderms, bivalves) the bakevelliid fauna of the Romualdo Formation can be tightly correlated with that of the Riachuelo Formation, supporting a paleogeographic scenario with a marine ingression flooding the Araripe Basin from the southeast, probably via the seaway developed in the Reconcavo-Tucano basin area. Finally, sedimentologic, stratigraphic and paleontological data indicates that the fate of the bakevelliids in the Romualdo Formation was linked to the onset of continentalization of the Araripe Basin. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Pteriomorphian bivalves; Shell beds; Lower Cretaceous seaway; Santana Group; Gondwana breakup